Latin poetry and conductus rhythm in medieval France - Page, Christopher 1952- (London Royal music association, 1997)
Conductus repertory of the twelfth and thirteenth centuries comes under re-investigation in this study. Christopher Page seeks to revise certain opinions about medieval Latin poetry which some exponents of modal theory have entertained. The book develops a view that spoken performances and sung performances of this repertory had their own distinct traditions, and that the most acceptable method of transcription for many conducti is a rhythmically neutral one which signals the wide range of possible rhythmic solutions to performance of these songs.
Keywords: Middle Ages (500-1400); Poetry; Music history; Music performance technique; Song; Catholicism; Latin; France